2013
DOI: 10.1039/c2ra22477a
|View full text |Cite
|
Sign up to set email alerts
|

CuFe2O4 nanoparticles as a highly efficient and magnetically recoverable catalyst for the synthesis of medicinally privileged spiropyrimidine scaffolds

Abstract: CuFe 2 O 4 nanoparticles as a highly efficient and magnetically recoverable catalyst for the synthesis of medicinally privileged spiropyrimidine scaffolds3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…The progress of the catalytic reaction was monitored by thin layer chromatography. 2 O with molar ratio of 1:2 in basic solution, as reported by Dandia et al [16].…”
Section: Materials and Instrumentationmentioning
confidence: 77%
“…The progress of the catalytic reaction was monitored by thin layer chromatography. 2 O with molar ratio of 1:2 in basic solution, as reported by Dandia et al [16].…”
Section: Materials and Instrumentationmentioning
confidence: 77%
“…In the earlier studies of the three-component reactions of amines and formaldehyde with β-diketones, β-keto esters 9 or cyclohexanone, 11,20 double aminomethylation was observed to occur at the -carbon atom. Six molecules of reactants were involved and six new covalent bonds were formed in this one-pot, threecomponent reaction.…”
Section: Resultsmentioning
confidence: 99%
“…16 The advantages offered by lactic-acid catalysis prompted us to make some preliminary experiments of its use with compounds other than thioamides, and, thus, to find out if it has a more universal applicability to the Mannich-type MCRs. Cyclohexanone was selected as the model reagent since its reactions with aromatic amines and formaldehyde have been studied earlier by numerous authors [9][10][11][12]20 in investigations using both typical and unusual catalysts. The reactions with p-tolylamine, p-bromoaniline, and p-nitroaniline were carried out by us at room temperature in a DMSO solution and, in the case of p-tolylamine, also in ethanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several work on different types of spinel were made, for example Nakashima et al [4] are evaluated the degree of cation disordering in spinel Zinc ferrite ZnFe 2 O 4 thin film, using a first principles method, they performed the theoretical simulations of X-ray Absorption Fine Structure (EXAFS) and X-ray Absorption Near Edge Structure (XANES) spectra at the Zn K edge and they concluded that about 60% (x=0.6) of Zn 2+ ions reside on the B sites in the ZnFe 2 O 4 thin film. The structural evolution and magnetic properties of nanostructured copper ferrite, CuFe 2 O 4 ,and Nickel ferrite NiFe 2 O 4 have been investigated also, by X-Ray diffraction as cited in [5], [6]. They are used as a catalyst [7] and humidity sensor [8].…”
Section: Introductionmentioning
confidence: 99%